2015
DOI: 10.15517/rbt.v63i4.18022
|View full text |Cite
|
Sign up to set email alerts
|

Floral and reproductive biology of Vaccinium meridionale (Ericaceae) in the Eastern Andes of Colombia.

Abstract: Floral and reproductive biology of Vaccinium meridionale (Ericaceae) in the Eastern Andes of Colombia. Vaccinium meridionale is a wild plant producing edible fruits in the mountain areas of Northern South America. However, the fruits of this species has been under an unsustainable extraction and there is a growing interest of establishing this species as a crop; nevertheless, the information about its breeding system is scarce, which is essential for its sustainable management and conservation. This research a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 37 publications
0
8
0
3
Order By: Relevance
“…Las especies cultivadas de Vaccinium (arándanos) se desarrollan en zonas climáticas con una temperatura media del aire entre 7 y 33 °C (Ormazábal et al, 2020) una precipitación anual entre 900 y 1300 mm y un régimen de un periodo lluvioso y un seco (Chamorro & Nates, 2015). Para el desarrollo de estas especies, el suelo debe tener un pH entre 4 y 5, de textura arenosa, arcillosa o franco-arenosa (Lambí et al, 2012;Muñoz-Vega et al, 2017;Ormazábal et al, 2020).…”
Section: Condiciones Edafoclimáticas De Vacciniumunclassified
See 1 more Smart Citation
“…Las especies cultivadas de Vaccinium (arándanos) se desarrollan en zonas climáticas con una temperatura media del aire entre 7 y 33 °C (Ormazábal et al, 2020) una precipitación anual entre 900 y 1300 mm y un régimen de un periodo lluvioso y un seco (Chamorro & Nates, 2015). Para el desarrollo de estas especies, el suelo debe tener un pH entre 4 y 5, de textura arenosa, arcillosa o franco-arenosa (Lambí et al, 2012;Muñoz-Vega et al, 2017;Ormazábal et al, 2020).…”
Section: Condiciones Edafoclimáticas De Vacciniumunclassified
“…El género Vaccinium es un frutal perenne de la familia de las Ericáceas que comprenden 450 especies (Llerena et al, 2014;Hurkova et al, 2019). Las especies cultivadas de Vaccinium son originarias del hemisferio Norte (USDA, 2002;Gonzáles et al, 2017), mientras que las especies silvestre de Vaccinium se encuentran en el neotrópico y distribuidas entra en los páramos de los Andes de América del Sur (Coba-Santamaría et al, 2012, Chamorro & Nates, 2015. Estas especies crecen y desarrollan entre los 1500 y 4700 m.s.n.m., en temperaturas que oscila entre 3 y 17 °C, suelos ácidos con un pH entre 4 y 5, y la presencia de microorganismos benéficos que permiten la buena adaptación de los cultivos (Camacho, 2013;Cobo et al, 2016;Ormazábal et al, 2020).…”
Section: Introductionunclassified
“…In other Vaccinium, it has been expressed that the periods of flowering and ripening of fruits may vary according to the year and the location (Antunes et al, 2008). In the zone of San Miguel de Sema (Boyacá), there are two periods of flowering, the first from February to April and the second from July to September; likewise, the individuals that bloom in each period are different (Chamorro, 2014). In V. corymbosum a swollen bud that will give rise to the flowers was described as the beginning of the inflorescence formation (Meyer and Prinsloo, 2003).…”
Section: Development Of the Inflorescence (Id) As Seen Inmentioning
confidence: 99%
“…Regarding the reproductive phase of this plant (FD and BD), Chamorro and Nates-Parra (2015), in Guachetá (Cundinamarca) and San Miguel de Sema (Boyacá), found that a bud develops completely when its flowers bloom, 18 days after beginning its formation and six days later the senescence of this organ occurs. However, Chamorro (2014) stated that the flowers' duration was only six to ten days, which it is considered a long floral longevity characteristic of the Ericaceae family (Primack, 1985), and these are mechanisms to increase the attraction of pollinators. Rathcke (2003), Torres-Díaz et al (2011), Chamorro (2014) and Chamorro and Nates-Parra (2015) found that the species produces a high quantity of flowers and low fruit production, which has been evidenced by selective abortion of self-pollinated fruits.…”
Section: Development Of Berries (Bd)mentioning
confidence: 99%
“…Este fruto crece en altitudes de (2200-3400 m s.n.m.) [5,6] y se puede considerar como una fruta rica en compuestos interesantes, antocianinas y flavonoides, los cuales contienen compuestos antioxidantes [7], con estructuras químicas que presentan algunas características que los hacen idóneos para estabilizar o desactivar radicales libres en el cuerpo humano [2].…”
Section: Introductionunclassified